Effect of chain architecture on the phase transition of star and cyclic poly(N‐isopropylacrylamide) in water. Issue 20 (27th June 2016) - Xue, Na; Qiu, Xing‐Ping; Chen, Yougen; Satoh, Toshifumi; Kakuchi, Toyoji; Winnik, Françoise M.
ABSTRACT: The heat‐induced phase transition of aqueous solutions of Poly( N ‐isopropylacrylamide) (PNIPAM) in water is examined for a four‐arm PNIPAM star ( s ‐PNIPAM), a cyclic PNIPAM ( c ‐PNIPAM), and their linear counterparts ( l ‐PNIPAM) in the case of polymers (1.0 g L −1 ) of 12, 700 g mol −1  < M n  < 14, 700 g mol −1 . Investigations by turbidity, high‐sensitivity differential scanning calorimetry (HS‐DSC), and light scattering (LS) indicate that the polymer architecture has a strong effect on the cloud point ( T c : decrease for s ‐PNIPAM; increase for c ‐PNIPAM), the phase transition enthalpy change (Δ H decrease for s ‐PNIPAM and c ‐PNIPAM), and the hydrodynamic radius of the aggregates formed above T c ( R H : c ‐PNIPAM <  s ‐PNIPAM <  l ‐PNIPAM). The properties of s ‐PNIPAM are compared with those of previously reported PNIPAM star polymers (3 to 52 arms). The overall observations are described in terms of the arm molecular weight and the local chain density in the vicinity of the core of the star, by analogy with the model developed for PNIPAM brushes on nanoparticles or planar surfaces. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 2059–2068. Abstract : Star PNIPAMs bearing a few arms of molecular weight lower than a critical value undergo a one‐step phase transition exhibiting unimodal endotherms. When the local chain density of PNIPAM around the core is very high, and/or the molecular weight of the arm exceeds a threshold value, the phase separation of multi‐arm star‐like PNIPAM takes place in two steps leading to bimodal endotherms.